(untitled) (International Journal of Engineering and Computer Science, 2017)
The progression of an economy is significantly dependent upon deployment as well as optimum utilization of resources and most importantly operational efficiency of the various sectors, of which banking sector pla ys a very vital role. Banking sector helps in stimulation of capital formation, innovation and monetization in addition to facilitation of monetary policy. It is imperative to carefully evaluate and analyze the performance of banks to ensure a healthy financial system and an efficient economy. Performance measurement is the most important activity of a management’s control function of any organization.